Memotivasi Guru dalam Pembuatan Karya Tulis Ilmiah di Kecamatan Karangpucung - Sigit Andi Prasetya Dinata; Dwi Setiawan; Agung Sholehudin (Jurnal DIKMAS, 2023)
The creation of scientific papers by teachers has an important role in professional development and improving the quality of education. However, many teachers face various challenges in producing scientific papers, such as lack of time, writing skills, and motivation. This article discusses the importance of motivating teachers to be active in scientific writing, both as a means of self-development and as a contribution to science. Through the right motivation, teachers can be more encouraged to be involved in research and writing, which in turn can increase their competence and have a positive impact for learning at school. Some strategies for motivating teachers include writing training, providing incentives, support from institutions, and establishing a scientific community that supports collaboration. By facilitating and motivating teachers in writing scientific papers, it is hoped that a stronger academic culture will be created among educators, as well as improving the overall quality of education.